On weighted Bochner-Martinelli residue currents - Wulcan, Elizabeth (Mathematica Scandinavica, 2012)
We study the weighted Bochner-Martinelli residue current R^p(f) associated with a sequence f=(f_1,…,f_m) of holomorphic germs at 0C^n, whose common zero set equals the origin, and p=(p_1,…, p_m)N^m. Our main results are a description of R^p(f) in terms of the Rees valuations of the ideal generated by (f_1^p_1,…, f_m^p_m) and an explicit description of R^p(f) when f is monomial. For a monomial sequence f we show that R^p(f) is independent of p if and only if f is a regular sequence.